FRI0422 Role of the prolyl 3-hydroxylase leprel1 in fibrosis. (12th June 2018) - Lopez, H.; Abdi Ahmed, B.; Abraham, D.; Bozec, L.; Denton, C.; Strange, A.; Martin, G.; Stratton, R.
Abstract : Background: Three prolyl 3-hydroxylase enzymes, LEPRE1, LEPREL1 and LEPREL2, are known to modify prolines in certain sequences in the C-terminal helical region of the polypeptide chains of procollagens converting them to 3-hydroxyproline residues. This modification appears to facilitate correct alignment of the chains in forming the triple helical domains of the procollagen molecules prior to secretion. Increased deposition of triple helical collagen and other extracellular matrix (ECM) proteins by activated fibroblasts underlies pathological fibrosis in systemic sclerosis (SSc), and may be dependent on prolyl 3-hydroxylase activity as a rate-limiting step. Objectives: The objectives of this study were: 1) to screen candidate genes with large first introns containing regulatory elements for association with systemic sclerosis (SSc) through copy number variation (CNV), 2) to study the lead candidate gene LEPREL1 further, as a fibrosis-related factor in genetically modfied mice subject to bleomycin induced skin fibrosis, 3) to determine the levels of LEPREL1 protein in SSc and control fibroblasts and measure possible induction by profibrotic factors, and 4) measure the effect of LEPREL1 gene editing on triple helical collagen secretion by SSc disease fibroblasts. Methods: DNA samples from SSc patients and controls were assayed by qPCR for CNVs within regulatory regions of 40 candidate genes. The lead candidate, LEPREL1 was studied further through tagging SNP analysis, of rs7612998, rs1447936, s1018343, s696065, in 564 SSc and 627 controls. In wild type (WT), GPVI -/-single knockout (SKO) or LEPREL1-/- GPVI -/-double knockout (DKO) mice skin fibrosis was initiated by daily subcutaneous bleomycin for 14 days (LEPREL1-/- embryonically lethal due to placental thrombosis). Skin fibrotic lesions sampled on day 21 were analysed by histology and picrosirius red stain. SSc and control skin fibroblasts grown from forearm skin biopsies, were cultured at passage 3–5, with or without the pro-fibrotic TGFbeta, or with or without estradiol in cells grown in oestrogen depleted conditons (no phenol red). LEPREL1 was assayed by Western blot. CRISPR/Cas9 was used to edit the LEPREL1 gene in SSc skin fibroblasts. Results: Initial screening of candidate genes revealed a weak statistical association between a first intron CNV nsv514192 and SSc susceptibility in males (p<0.028). However SNP analysis demonstrated that a haplotype, identified as CTAA across the 4 SNPs, was associated with increased risk of SSc development (OR 3.45, p<0.0023). This allele opens a FOXA1 site in the first intron and was seen predominantly in females. In cultured dermal fibroblasts LEPREL1 protein levels were raised in SSc samples and induced to SSc levels in control fibroblasts by culture with TGFbeta. Estradiol also induced LEPREL1 and collagen I protein. In genetically modified LEPREL1 knockout mice, resistance to bleomycin skin fibrosis was seen (figure 1). Silencing of LEPREL1 in SSc fibroblasts by CRISPR/Cas9 preferentially reduced triple helical collagen I secretion. Conclusions: The prolyl 3-hydroxylase LEPREL1 is confirmed as a fibrosis-related gene associated with SSc susceptibility. Small molecule inhibitors of this endoplasmic reticulum enzyme may limit the overproduction of collagen as a therapy for fibrosis. Disclosure of Interest: None declared